How Informality Can Address Emerging Issues: Making the Most of the G7. Issue 2 (29th March 2019) - Morin, Jean‐Frédéric; Dobson, Hugo; Peacock, Claire; Prys‐Hansen, Miriam; Anne, Abdoulaye; Bélanger, Louis; Dietsch, Peter; Fabian, Judit; Kirton, John; Marchetti, Raffaele; Romano, Simone; Schreurs, Miranda; et al.
Abstract : The G7 should address new, unprecedented and highly disruptive issues that characterise our complex world, rather than well‐understood international problems that fit into existing categories. We argue that the G7 can do this by playing to its strengths – informality and like‐mindedness in particular – in addressing emerging and transversal issues such as Artificial Intelligence (AI) and cryptocurrencies.